Immunological Defects in Neonatal Sepsis and Potential Therapeutic Approaches - Raymond, Steven L.; Stortz, Julie A.; Mira, Juan C.; Larson, Shawn D.; Wynn, James L.; Moldawer, Lyle L. (Frontiers in Pediatrics, 2017)
Despite advances in critical care medicine, neonatal sepsis remains a major cause of morbidity and mortality worldwide, with the greatest risk affecting very low birth weight, preterm neonates. The presentation of neonatal sepsis varies markedly from its presentation in adults, and there is no clear consensus definition of neonatal sepsis. Previous work has demonstrated that when neonates become septic, death can occur rapidly over a matter of hours or days, and is generally associated with inflammation, organ injury, and respiratory failure. Studies of the transcriptomic response by neonates to infection and sepsis have led to unique insights into the early proinflammatory and host protective responses to sepsis. Paradoxically, this early inflammatory response in neonates, although lethal, is clearly less robust relative to children and adults. This suggests that the neonate must be exquisitely more sensitive to the inflammatory response than adults. Similarly, the expression of genes involved in host protective immunity, particularly neutrophil function, is also markedly deficient. As a result, neonates have both a diminished inflammatory and protective immune response to infection which may explain their increased risk to infection, and their reduced ability to clear infections. Such studies imply that novel approaches unique to the neonate will be required for the development of both diagnostics and therapeutics in this high at risk population.